The happiness gap between transition and non-transition countries - Ekaterina Skoglund (IZA World of Labor, 2017)
Since 1989, post-communist countries have undergone profound changes in their political, economic, and social structures and institutions. Across a range of development outcomes—in terms of the speed and success of reforms—transition is an “unhappy process.” The “happiness gap,” i.e. the difference in average happiness levels between the populations of transition and non-transition economies, is closing, but at a slower pace than the process of economic convergence. Economic growth, as the determinant of a country's collective well-being, has been superseded by measurements of institutional quality and social development.
Keywords: D02; I31; P20; 330; happiness gap; subjective well-being; transition; institutions